Standardization of bottled tilapia (Oreochromis niloticus) in coconut sauce - Molo, Lito Monserate (Iloilo College of Fisheries and Ocean Sciences, U.P. Visayas, 2006)
A study on standardization of the formulation, pre-processing treatment and processing schedule of bottled tilapia (oreochromis niloticus) in coconut sauce ws conducted. In the determination of standardized formulation of the product, different levels of carrageenan (0.1%, 0.2! and 0.3%) were added to the coconut sauce in an attempt to answer the problem associated with the coagulation of the sauce during the thernmal process. Different combinations of drying time and frying (1 hr drying, without frying; 2 hr drying without frying;1 hr drying with frying; 2 hr drying with frying) were tested in order to determine the appropriate combination that can result to more acceptable product. In the standardization of the process schedule for bottled tilapia in coconut sauce, samples were subjected at a heat penetration study using different time temperature combinations, namely, 30 min at 15 psi, 45 psi, and 90 min at 10 psi. bottled samples were analysed via sensory evaluation of 6 semi-trained panellists, cut out tests and microbial tests. Resultsshowed that the bottled tilapia samples, with or without carrageenan added, in the coconut sauce were not significantly different (~a=0.05) however, based on the appearance of the sample in the bottle, the oil was completely emulsified in samples treated with 0.1% and 0.1% carrageenan. Hence, sample added with 0.1% carrageenan was employed in the succeeding tests. It was also noted that frying significantly affects the organoleptic characteristics of the product, extending the drying time could increase the over-all acceptability scores of the product but it does not produce any significant difference to merit a recommendation that drying time should be increased from 1 to 2 hr. Heat penetration study revealed that the SHP of the product is at the point midway between ¾ inch from the bottom and geometric center of the bottle and that the bottled tilapia in coconut sauce exhibits broken heating curve. In terms of sensory scores, although no significant difference was noted in sampkles processed using different time temperature combinations, it appears that processing tilapia in coconut sauce should follow a processing schedule of 45 min at 15 PSI. this is due to the relatively higher (but nor necessarily statisticallu significant) mean acceptability scores of the sample processed using this schedule, as compared to the other combinations tested (i..e 30 min at 15 psi and 90 min at psi0. The processing schedule of 45 min at 15 psi has an Fo value of more than the required minimum Fo value clostridium botulinum. This implies that the processing schedule obtained in this study is enough to render the product commercially sterile. This findings was supported by the negative growth of gas producing and acid microoganisms in the samples, as evidenced in the microbial tests conducted.
Thesis
Keywords: Tilapia -- Preservation; Bottled Tilapia; Oreochromis niloticus